Yield and nutrient augmentations in wheat: Application of plasma processed zinc - Mamunur Rashid; M R Talukder; Monzur Hossain (PLoS ONE, 2026)
Billions of people worldwide suffer from hidden hunger caused by deficiencies in essential micronutrients, particularly zinc (Zn). Conventionally, Zn deficiency in humans has been addressed through dietary supplementation; however, agronomic biofortification offers a sustainable alternative. Plasma-assisted technology has recently emerged as a promising approach for enhancing Zn fortification in crops, although the underlying mechanisms governing Zn uptake and assimilation remain insufficiently understood. The present study investigates the mechanisms involved in plasma-mediated Zn fortification and its effects on plant physiology. Field experiments were conducted on wheat ( Triticum aestivum L.) using plasma-processed ZnO, ZnSO₄, and their mixture (ZnO + ZnSO₄). A concentration of 200 ppm ZnO (ZnOTFS), ZnSO₄ (ZnSO₄TFS), and their mixture ((ZnO + ZnSO₄)TFS) was prepared in water and subsequently treated using plasma to generate plasma-processed water (PPW). The resulting solutions were applied as foliar sprays at an early growth stage of wheat plants. Growth parameters and carotenoid concentrations showed significant enhancement in plants receiving plasma-treated foliar applications compared to controls. Moreover, plasma-assisted foliar spraying reduced oxidative stress and significantly enhanced antioxidant enzyme activities, including catalase (CAT), ascorbate peroxidase (APX), and superoxide dismutase (SOD), in both leaves and roots. The concentrations of Zn and Fe in plant tissues increased by 50.35% and 28.81%, and by 94.30% and 62.34%, respectively, compared to the control and non-plasma-treated (ZnO + ZnSO₄) foliar spray treatments. In addition, grain quality and yield improved by 59%, 34%, and 26% relative to the control, PPW alone, and non-plasma-treated (ZnO + ZnSO₄) foliar spray treatments. These results demonstrate that plasma-assisted Zn fortification significantly enhances micronutrient accumulation, antioxidant defence, and yield attributes in wheat, highlighting plasma technology as a viable and sustainable strategy for combating micronutrient malnutrition.